The effects of killer cell immunoglobulin-like receptor (KIR) genes on susceptibility to severe COVID-19 in the Iranian population - Narges Karami; Shaghik Barani; Mona Fani; Seppo Meri; Reza Shafiei; Kurosh Kalantar (BMC Immunology, 2024)
Abstract Background Variations in the innate and adaptive immune response systems are linked to variations in the severity of COVID-19. Natural killer cell (NK) function is regulated by sophisticated receptor system including Killer-cell immunoglobulin-like receptor (KIR) family. We aimed to investigate the impact of possessing certain KIR genes and genotypes on COVID19 severity in Iranians. KIR genotyping was performed on 394 age/sex matched Iranians with no underlying conditions who developed mild and severe COVID- 19. The presence and/or absence of 11 KIR genes were determined using the PCR with sequence specific primers (PCR-SSP). Results Patients with mild symptoms had higher frequency ofKIR2DS1 (p = 0.004) and KIR2DS2 (p = 0.017) genes compared to those with severe disease. While KIR3DL3 and deleted variant of KIR2DS4 occurred more frequently in patients who developed a severe form of the disease. In this study, a significant increase of and B haplotype was observed in the Mild group compared to the Severe group (respectively, p = 0.002 and p = 0.02). Also, the prevalence of haplotype A was significantly higher in the Severe group than in the Mild group (p = 0.02). Conclusions These results suggest that the KIR2DS1, KIR2DS, and B haplotype maybe have a protective effect against COVID-19 severity. The results also suggest the inhibitory gene KIR2DL3 and haplotype A are risk factors for the severity of COVID-19.